Tác động của kiểm soát tham nhũng đến chi tiêu chính phủ - Nguyễn Thành, Công; Trần Thị, Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Using a panel of 82 countries over the years 1996–2019, this paper examines the impact of control of corruption on government expenditure. The authors find that increased control of corruption reduces government expenditure. However, the magnitude of this effect is relatively small. Digging deeper into components of government expenditure, the regression results show that control of corruption reduces government spending on public services, economic affairs, and social welfare, of which the decline in spending on social welfare is the strongest. In spending on social welfare, the negative impact of control of corruption on social protection is more pronounced than those of spending on health and education. In contrast, spending on defence and safety and order does not appear to be affected by control of corruption. The authors also find that increased control of corruption has a stronger impact on developing countries than on developed countries.
Keywords: Control of corruption; Government expenditure; GMM model